2014
DOI: 10.1056/nejmoa1408758
|View full text |Cite|
|
Sign up to set email alerts
|

Fractional Flow Reserve–Guided PCI for Stable Coronary Artery Disease

Abstract: In patients with stable coronary artery disease, FFR-guided PCI, as compared with medical therapy alone, improved the outcome. Patients without ischemia had a favorable outcome with medical therapy alone. (Funded by St. Jude Medical; FAME 2 ClinicalTrials.gov number, NCT01132495.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
623
2
19

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 966 publications
(657 citation statements)
references
References 29 publications
13
623
2
19
Order By: Relevance
“…cSE‐WMP results might be useful for the decision to revascularize or not, similar to what fractional flow reserve (FFR) studies have recently proposed 26, 27, 28. Our findings point in the same direction to what has been observed with invasive FFR; such multicenter studies prospectively demonstrated that FFR is prognostically useful to proceed to revascularization, but in patients already selected to undergo diagnostic coronary angiography, although they fell short of demonstrating a benefit regarding hard events, death and MI, since in the FAME 2 study (Fractional Flow Reserve Versus Angiography for Multivessel Evaluation) the FFR‐guided percutaneous coronary revascularization arm was favored on comparison of the primary composite end point of death, MI, and target vessel revascularization, but such finding was driven by urgent target vessel revascularization 28, 29.…”
Section: Discussionsupporting
confidence: 54%
“…cSE‐WMP results might be useful for the decision to revascularize or not, similar to what fractional flow reserve (FFR) studies have recently proposed 26, 27, 28. Our findings point in the same direction to what has been observed with invasive FFR; such multicenter studies prospectively demonstrated that FFR is prognostically useful to proceed to revascularization, but in patients already selected to undergo diagnostic coronary angiography, although they fell short of demonstrating a benefit regarding hard events, death and MI, since in the FAME 2 study (Fractional Flow Reserve Versus Angiography for Multivessel Evaluation) the FFR‐guided percutaneous coronary revascularization arm was favored on comparison of the primary composite end point of death, MI, and target vessel revascularization, but such finding was driven by urgent target vessel revascularization 28, 29.…”
Section: Discussionsupporting
confidence: 54%
“…Although the unequivocal benefit of FFR‐guided revascularization over angiographic guidance has been established,9, 10, 11 it should be noted that FFR is determined under the assumption of minimal and constant microvascular resistance. Our results suggest that microvascular resistance independently and significantly influences visual‐functional mismatch and reverse mismatch in a large study population with intermediate epicardial coronary stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, cumulative evidence suggests that angiographically determined anatomical stenosis severity often underestimates or overestimates the functional significance of lesions 5, 6, 7. Fractional flow reserve (FFR) is currently the standard for decision‐making regarding revascularization in the catheter laboratory and has become part of the clinical guidelines for the assessment of the physiological significance of epicardial coronary stenosis based on sound concepts and randomized clinical trials 8, 9, 10, 11. However, FFR evaluation is still underutilized; instead, coronary angiography is widely used as a gatekeeper for decision‐making of revascularization even in large clinical trials 2, 12.…”
Section: Introductionmentioning
confidence: 99%
“…FFR and CFR are both well‐validated physiological indices for guiding PCI indication 2, 3, 4, 11. A recent study also suggested that FFR measured after PCI has prognostic value, with an inverse relationship to subsequent clinical events 5.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional flow reserve (FFR) is the standard in decision making for revascularization in the catheter laboratory and has become a part of the clinical guidelines for assessing the physiological significance of epicardial coronary stenosis based on a sound concept and randomized clinical trials 1, 2, 3, 4. A recent study also suggested that FFR measured after percutaneous coronary intervention (PCI) has prognostic value, with an inverse relationship to subsequent clinical events 5.…”
Section: Introductionmentioning
confidence: 99%